2013
DOI: 10.4329/wjr.v5.i3.51
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative abdominal ultrasound in oncologic imaging

Abstract: Significant advances in ultrasound technology have created new opportunities for its use in oncologic imaging. The advent of new transducers with focal beam technology and higher frequency has solidified the role of intraoperative sonography (IOUS) as an invaluable imaging modality in oncologic surgery of the liver, kidneys and pancreas. The ability to detect and characterize small lesions and the precise intraoperative localization of such tumors is essential for adequate surgical planning in segmental or lob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 28 publications
(65 reference statements)
0
20
0
1
Order By: Relevance
“…It is interesting to note that definitive histopathological diagnoses excluded the possibility of a neoplasm in some cases in the present study, including a number of lesions identified only by IOUS. These results reinforce the need for histopathological evaluation of all suspected lesions, identified by preoperative transabdominal ultrasound or IOUS (GASCHEN, 2009;MARCAL et al, 2013). The use of IOUS during abdominal surgery allows for the direct application of a highfrequency transducer on the surface of the organ(s) of interest, with no obstacle in the abdominal wall to the penetration of sound waves.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…It is interesting to note that definitive histopathological diagnoses excluded the possibility of a neoplasm in some cases in the present study, including a number of lesions identified only by IOUS. These results reinforce the need for histopathological evaluation of all suspected lesions, identified by preoperative transabdominal ultrasound or IOUS (GASCHEN, 2009;MARCAL et al, 2013). The use of IOUS during abdominal surgery allows for the direct application of a highfrequency transducer on the surface of the organ(s) of interest, with no obstacle in the abdominal wall to the penetration of sound waves.…”
Section: Discussionmentioning
confidence: 64%
“…The ability of IOUS to provide real-time imaging of the organs of interest, with accurate small lesion detection and characterization, establishes the important role of IOUS in intraoperative guidance for either biopsy or resection (MARCAL et al, 2013). However, differentiation between malignant and benign lesions is not possible with only IOUS evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations